RECOVERY OF SCAPULOHUMERAL PERIARTHRITIS AT A HANDBALL PLAYER - Ioana CURIŢIANU (Editura Universitatii Transilvania din Brasov, 2018)
Kinesiology is a science that deals with the study of the movement of living organisms and structures that participate in these movements [4]. This research aims to demonstrate the utility of kinetotherapeutic means by methods and programs with individualized, standardized and rationalized elements depending on the subject's particularities and the gravity of the case, bring benefits and a rapid and efficient recovery of the patient with scapulohumeral periarthritis. The clinical trial was performed on a 30-year-old practitioner of the handball game and was run for six months. The interpretation of the results obtained from the recovery program is based on the patient's evolution, both physically and psychologically. The recovery programs have been developed and used structured in four phases, depending on the patient's evolution. The athlete presented scapulohumeral periarthritis (simple painful shoulder), accusing persistent pain in the shoulder, located in the upper muscle area.